A Numerical Integration Method for Calculating the Bit Error Rate of Time-Modulated Array - Kexin Wang; Jian Zhang; Gang Xin; Xue Lei; Jun Gao; Tianpeng Li (IEEE Open Journal of Antennas and Propagation)
In this paper, we present a novel approach for computing the bit error rate of time-modulated array using the Laplace inversion integral. We express the bit error rate as a Laplace inversion integral and select the integration path using the saddle point method. The integration result is obtained through numerical integration, and we derive the upper bound of the truncation error. The time-modulated array under consideration includes a single pole double throw switch array, which can independently exist in two states. This calculation method can be readily extended to time-modulated arrays with multiple states. To assess the accuracy of this method, we provide an example for verification and comparison with the results of exact calculations. The findings demonstrate consistency between the two methods while significantly reducing computational complexity.